Beyond Administrative Sanctions: Reforming Insider Trading Regulation to Strengthen Investor Protection in Indonesia - Sugianto, Fajar; Tokuyama, Shintaro (Jurnal Media Hukum, 2025)
Insider trading in Indonesia continues to expose structural weaknesses in capital market regulation, even after the enactment of the Strengthening Financial Sector (SFS) Law in 2023. Although the law expands the Financial Services Authority’s (FSA) supervisory powers, it fails to address core gaps that undermine legal certainty and investor protection. This study explores two main questions: (1) whether victims of insider trading are genuinely protected under the current framework, and (2) what doctrinal and institutional reforms are needed to build a more effective system. Using a normative legal research method, the study finds that the adoption of the una via principle has not strengthened enforcement. Most insider trading cases are still resolved through administrative sanctions, offering limited deterrence. Furthermore, inconsistencies between the SFS Law and Article 102 of the Capital Market Law perpetuate fragmented enforcement among regulators, prosecutors, and courts. This study contributes by integrating constitutional principles, legal theory, and comparative perspectives to show why Indonesia’s insider trading regime remains incomplete. The PT Perusahaan Gas Negara (PGN) case illustrates how delayed disclosure and a narrow definition of “insider” undermine market trust, highlighting the need for both procedural and substantive reforms.